Information and telecommunication infrastructure and economic growth: an experience from Nigeria - Oyeniran, Wasiu Ishola; Onikosi-Alliyu, Saidat (Serbian Journal of Management, 2016)
The study examines the effect of investment in telecommunication infrastructure on economic growth in Nigeria. Using time series data from 1980 and 2012, the study employs autoregressive distributed lag (ARDL) bounds testing approach proposed by Pesaran et al., (2001) to estimate the long run and short run effect of investment in telecommunication infrastructure on economic growth. The result from cointegration test showed presence of long run relationship between dependent and all explanatory variables. The study found foreign direct investment in information and communication technology more effective in improving and raising economic growth in Nigeria than government investment. The output from Chow breakpoint test shows that the liberalization of telecommunication industry introduced in 1992 has significant effect on economic growth in Nigeria. Therefore, it is imperative for Nigerian government to increase its spending on telecom  and attract more foreign investment in telecommunication in order to boost productivity and economic growth.